Funkcjonowanie polityków w nowych mediach – pomiędzy kreowaniem wizerunku a agresją elektroniczną (Politeja, 2013)
New media and politicians – between image creation and electronic aggressionNew Media brought new roles for all actors engaged in politics: politicians and their coworkers, potential voters and media itself. As users of new media are active politicians have broaden their scope of communication with an external environment and opportunities to construct their social image. Also the social control of general public and media over the politicians’ activities is nowadays much stronger. Unfortunately some features of new media may also be utilized in negative actions such as so called electronic aggression against a politician or his/her image. In this context the new media play a negative role for a politician using them to build his/her image.